Características da condução do samba pelo baterista Milton Banana em seu conjunto de música instrumental - Moraes, Felipe Diego de (2020)
The present work investigates drums’ performance and aims to understand the musical idiom of the drummer Milton Banana in samba. Articulating the fields of history and musicology, the way to reach this goal is through an analysis of the musician's performance with his instrumental set Milton Banana Trio, through the matrices presented in the thesis of Professor Doctor Leandro Barsalini (2014), in his thesis, the teacher offers tools for the recognition of patterns of Samba performance on drums, through the combination of percussive functions: phrasing, driving and marking. Through the combination of functions, we will recognize the stylistic matrices, namely: samba batucado, brushed samba, samba with conduction and phrasing. With the foundations for idiomatic analysis presented, we transcribe the part of the battery corresponding to each matrix listed in the dissertation, to analyze and reflect on the performance of the musician. For each matrix, we reflect diferently, either seeking the drummer's dialogue with the other members of the group, or analyzing it from the perspective of the constituent functions of the matrix addressed. After the analysis we came to the conclusion, the driving style of drummer Milton Banana in samba has a predominance in the samba matrix of conduction plate.